Myths of skin whitening agents and the emerging use of glutathione - Nadeem, Muhammad (Journal of Fatima Jinnah Medical University, 2018)
From light-skinned goddess portrayed in ancient religious scenes, pearl gulping practices in China, turmeric functions in India to clay application in Africa, history has been hued by our faulty aversion for the darker skin shades.1 The appeal of a more translucent appearance is implied by practices dating from Cleopatra's milk showers to Queen Elizabeth I's use of ceruse face powder (a mixture of lead and vinegar).2 The Asian culture associates fairer skin with feminine beauty, racial superiority and power. Media and advertisements have unequivocally connected more skin fairness to magnificence, sentiment and even career success. Skin, hair and eye color is hereditarily controlled by the measure of melanin found in the top layers of skin.3 Skin whitening creams most often give the skin an orange hue and when the sun hits hard on the unsupported hypo-pigmented skin, the yellowish orange hue will turn dark again. Most of these items, claim to be anti-melanin, are currently on sale since long, but with potentially adverse long-term outcomes. Skin lightening products available in the market contain a dangerous cocktail of harmful chemicals like mercury, hydroquinone and steroids, and so are extremely injurious to health.4 Products containing mercury may have serious side effects like neuronal damage, renal damage and anxiety/depression and decrease skin resistance to bacteria and fungi.4 Products containing hydroquinone may lead to uneven blue black pigmentation (ochronosis), liver damage and skin cancers, and those with corticosteroids can lead to hirsutism, skin atrophy, renal suppression, hypertension, infections, contact eczema and Cushing’s syndrome.5 A number of topical cosmeceutical agents containing hydroquinone, alpha and beta-hydroxy acids, tretinoin, mequinol, arbutin, vitamin C and magnesium ascorbyl phosphate are now in vogue for treatment of hyperpigmentation disorders and for skin lightening.